The Effect of Leadership Style, Organizational Culture and Compensation on Employee Engagement at Garment Companies in Bandung - Neneng Sofiyanti; Najmudin Najmudin (Westscience Press, 2023)
This study investigates how salary, organizational culture, and leadership style affect employee engagement in a Bandung-based clothing firm. Deductive reasoning is used in this study to get quantitative data from surveys. The results demonstrate that fair remuneration, a collaborative corporate culture, and transformational leadership style all strongly influence employee engagement in the apparel sector. The findings of this study emphasize the significance of improving employee engagement by fostering a favorable work environment and coordinating leadership behaviors, cultural values, and remuneration methods. These insights provide valuable guidance for garment companies in Bandung to optimize employee engagement and improve overall organizational effectiveness.